Aesthetics and Philosophy of the Performance Interpretation of the Author's Concept of a Musical Work - Vіtalіi ZAIETS; Oksana ZAIETS (Studia Universitatis Babeş-Bolyai. Musica)
The presented research is aimed at revealing the theoretical and philosophical methodological basis of the art of performance interpretation from the perspective of the procedural triad composer-performer-listener. In the process of interpretation, the performer acts as an active carrier of internal needs and motivations, which have a physiological, psychological, moral, and aesthetic as well as volitional nature. This division is quite conditional as these processes occur simultaneously and interact with each other. Each person is more or less inclined to a certain meaningful aspect, which forms an individual approach to the interpretation of the work. Thus, the needs of the performer (during the conscious search for the sound embodiment of the interpretation at the stage of practical implementation) resolve the most important issue: the ratio of the author's and performer's concepts.